Just ask a woman : - Quinlan, Mary Lou (John Wiley & Sons, 2003)
Just Ask a Woman is a powerful book about how to tap into female consumers' needs. Mary Quinlan, the founder of the premiere consultancy dedicated to marketing to women, has personally interviewed 3,000 women in the course of her research for Just Ask a Woman. Women are the decision-makers in an estimated eighty-five percent of household buying decisions, and yet far too often, products marketed specifically to them fail to connect with their needs. Here, Quinlan explores topics such as how women judge brands and advertising, how they make decisions, the effects of stress on their consumer behavior, and their increasing demands for service and communication. Quinlan rejects the traditional focus group approach in favor of highly energized and intimate talk sessions where women reveal their deeper feelings about products and services. In Just Ask a Woman marketers, brand managers, and advertisers will find a revelatory resource filled with ideas and action steps for building your brand with women-from a woman who has walked in a marketer's shoes.